Inadequacies in the comprehensive stomatologic care to children with deglutition disorders in primary health care - Dania Santos Prieto; Lianet Hurtado Santos; Olga Lidia Véliz Concepción (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction:  Deglutition is a complex activity of evolutionary character that requires of an appropriate stomatologic care to maintain the balance of the stomatognathic system.  Objective: To identify inadequacies in the comprehensive stomatologic care to children with deglutition disorders in primary health care.  Methods:  A descriptive and cross-sectional study was carried out, with mixed approach, of 24 comprehensive general stomatologists from Victoria Stomatologic Clinic in Santa Clara, Villa Clara province that were working during January-March, 2023 and had more than 3 years of professional experience, for which theoretical and empiric methods were used. The qualitative and quantitative analysis of the data was carried out by means of the absolute and relative frequencies.  Results: In the revised normative-methodological documents are not explicitly reflected all the promotion and prevention activities, as well as the necessary aspects for the diagnosis and treatment of patients with deglutition disorders. Most of those interviewed (83.3%)  identified deglutition as a habit; as long as, among the determining environmental factors there was little recognition of the  kid position when eating (20.8 %),  the use of  tablespoon and  glass (29.1 %) and nasal respiration (33.3 %). Equally, 50.0 % of the sample presented a medium level of knowledge.  Conclusions: There are inadequacies in the comprehensive stomatologic care to children with deglutition disorders in primary health care.